Dampak Perubahan Tutupan Lahan Terhadap Debit Puncak Das Tiro Berdasarkan Metode Rasional (The Impact of Land Cover Change on Peak Discharge in the Tiro Watershed Using the Rational Method) - Pradhipta Ertya Sakti; Hairul Basri; Purwana Satriyo (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2026)
Land cover changes play a significant role in influencing the hydrological response of watersheds. These changes can increase peak discharge, even in watersheds that are not classified as national rehabilitation priorities. The Tiro Watershed in Aceh Province experiences recurrent flooding, yet the quantitative study of its hydrological dynamics related to land cover changes is lacking. This study aimes to evaluate the impact of land cover changes on peak discharge  during the 2014 - 2024 period using the Rational Method. Spatial overlay analysis was conducted to identify land cover transitions and calculate the watershed runoff coefficients. Areal rainfall was calculated using the isohyet method with inverse distance weighting (IDW), followed by frequency analysis to determine planned rainfall for the the 2 to 100  year return period. Peak discharge was calculated using a Rational formula and validated with observed discharge data using Nash-Sutcliffe Efficiency (NSE). Results showed a 3,498.8 ha decrease in primary dryland forest, which increased the watershed runoff coefficient from 0.109 to 0.126 (15.6%). These changes resulted in a 15.6% increase in peak discharge across all return periods. The highest increase was 52.5 m³/s at the 100-year return period. Model validation results showed  NSE values of 0.77 in 2014 and 0.93 in 2024, considered good. These findings suggest that land cover dynamics primarily determine peak discharge variation in the Tiro Watershed during the study period. Keywords: land cover change; peak discharge; Rational Method; runoff coefficient; Tiro Watershed